An Overview of Fermatean Neutrosophic Graphs - Prasanta Kumar Raut; Surapati Pramanik; Bhabani S. Mohanty (Neutrosophic Sets and Systems)
Fermatean Neutrosophic graph theory plays a significant role in the modeling and organization of optimization problems. In real-world scenarios, uncertainty is often present due to undetermined or incomplete information. Consequently, experts face challenges in designing optimization problems using fuzzy graphs. To address concerns about inconsistency, unpredictability, and vagueness in graphical optimization problems, various expansions of graph mathematical concepts have been developed. One such expansion is the concept of Fermatean neutrosophic graphs, which effectively manage uncertainties associated with unspecified and inadequate data in optimization problems. This article explores different types of Fermatean neutrosophic graphs and their operations. Additionally, it provides a numerical example showcasing the application of Fermatean Neutrosophic Sets in decision-making. These operations serve as valuable tools for analyzing and manipulating neutrosophic graphs in optimization problems.